Review Article: The Effect of Adding Starfruit Extract (Averrhoa bilimbi L.) to Drinking Water on the Performance of Laying Quails - Meidita, Fadilla; Rahma, Nadia (Jurnal Tropicalanimal, 2024)
This article aims to review the effect of adding starfruit (Averrhoa bilimbi L.) extract to drinking water on the performance of laying quails. Previous studies have shown that starfruit extract contains bioactive compounds such as citric acid, flavonoids, and antioxidants, which act as natural acidifiers, enhancing digestion, nutrient absorption efficiency, and reducing oxidative stress in livestock. Several previous studies have demonstrated the significant impact of starfruit extract on production performance parameters, egg quality, and livestock health. However, not all studies have shown consistent results, especially in terms of feed consumption and body weight. This review was conducted through a literature analysis of reputable journals published over the past ten years. The findings reveal that administering starfruit extract at optimal concentrations (2.5%-5%) has the potential to improve egg white quality, Haugh Unit values, and optimize nutrient absorption in the digestive tract of quails. The addition of the extract also helps reduce livestock mortality and improves feed conversion efficiency. Nevertheless, some results indicate no significant effect on feed consumption and body weight. In conclusion, starfruit extract holds great potential as a natural additive to support more sustainable poultry production. These findings are expected to provide new scientific references for the development of environmentally friendly, locally-based plant additives that contribute to increased livestock productivity.